Successful conservative management of live cervical ectopic pregnancy: case report - Khithani, Juhi L.; Supe, Pradnya B.; Sarmalkar, Meenal S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Cervical ectopic pregnancy (CEP) is an exceptional type of ectopic pregnancy, representing <1% of the ectopic pregnancy with incidence 1:2500 to 1:12000. It can lead to life threatening complication and torrential bleeding and even necessitate the need for hysterectomy. A 30-year-old patient referred to Lokmanya Tilak Municipal Medical College with transvaginal sonography suggestive of live CEP. Because of patient’s stable condition, it was treated with ultrasound-guided intra-amniotic methotrexate administration. Day 1 β-HCG was 4200 IU/L, day 10 489 IU/L. Gradual decrease of β-HCG levels was coinciding with ultrasonographic finding of absence of gestational sac. During hospitalization, patient reported only minimal vaginal spotting on day 3 of treatment and discharged on day 10 with weekly β-HCG followup. CEP was managed conservatively without surgical intervention, preserving patient’s fertility. Timely detection of CEP and prompt action can save patients fertility with minimal or no surgical intervention.